2006
DOI: 10.1097/01.sap.0000200775.56263.2d
|View full text |Cite
|
Sign up to set email alerts
|

Perforating Arteries of the Gluteal Region

Abstract: Gluteal artery perforator flaps have gained popularity due to reliability, preservation of the muscle, versatility in flap design without restricting other flap options, and low donor-site morbidity. Today, free or local flaps based on the perforating arteries of the gluteal region are among the most commonly used procedures for the management of lumbosacral defects and autologous breast reconstruction. An anatomic study was carried out to investigate localization, dimension, and distribution of the perforator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 9 publications
0
14
0
4
Order By: Relevance
“…The location of inferior gluteal artery perforators is less definite and varies considerably in different studies [24,25], with one study reporting the IGA absent in 13.5 % of cases [20].…”
Section: Flap Design and Blood Supplymentioning
confidence: 97%
“…The location of inferior gluteal artery perforators is less definite and varies considerably in different studies [24,25], with one study reporting the IGA absent in 13.5 % of cases [20].…”
Section: Flap Design and Blood Supplymentioning
confidence: 97%
“…It emerges at the border of the sacrum at the junction of the medial one-third and lateral two-thirds of a line drawn between the PSIS and the apex of the greater trochanter of the femur [19]. Doppler flowmetry is useful for identifying perforators preoperatively [3,8]. Koshima et al [10] reported the reliability of the blood supply through perforator vessels of flaps that could reach the sacral area without problems.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da relevância no contexto do estudo anatômico a maioria destes estudos apresentou pequeno número de indivíduos estudados reduzindo seu peso na extrapolação dos resultados para a população [47,86] . Outros foram realizados em populações específicas como a coreana, podendo não ser representativos para populações ocidentais [103] .Por outro lado, os estudos realizados em cadáveres formolizados, permitem a análise das estruturas vasculares, porém dificultam a tomada de medidas das mesmas por causa da limitação da elasticidade dos tecidos [46] .…”
Section: Os Retalhos Fasciocutâneos Descritos Por Pontén Em 1981unclassified
“…Kankaya et al [46] , em estudo anatômico realizado em 8 cadáveres formolizados, relataram a presença média de 17 pedículos perfurantes por região glútea estudada. Dividiram a região glútea em 3 zonas de acordo com a densidade de vasos perfurantes, tendo a zona inferior cerca de 31,5% dos vasos.…”
Section: Os Retalhos Fasciocutâneos Descritos Por Pontén Em 1981unclassified
See 1 more Smart Citation